2017
DOI: 10.1136/jnnp-2017-316820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of known amyotrophic lateral sclerosis and frontotemporal dementia genes reveals a substantial genetic burden in patients manifesting both diseases not carrying the C9orf72 expansion mutation

Abstract: Our results indicate a high genetic burden underlying the co-occurrence of ALS and FTD and expand the phenotype associated with , and to FTD. A systematic screening of ALS and FTD genes could be indicated in patients manifesting both diseases without the expansion mutation, regardless of family history of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 41 publications
3
36
0
1
Order By: Relevance
“…Thus, their change of expression in ALS could be related with the pathology [190]. Moreover, mutations in ErbB4 have been described in autosomal dominant familial and sporadic forms of ALS [191] with concomitant frontotemporal dementia [192]. This supports a possible pathogenic role of ErbB4 in ALS [193].…”
Section: Erbbmentioning
confidence: 77%
“…Thus, their change of expression in ALS could be related with the pathology [190]. Moreover, mutations in ErbB4 have been described in autosomal dominant familial and sporadic forms of ALS [191] with concomitant frontotemporal dementia [192]. This supports a possible pathogenic role of ErbB4 in ALS [193].…”
Section: Erbbmentioning
confidence: 77%
“…The other (patient 14) had a prominent amygdalar gliosis. A detailed description of the neuropathological examination of this patient was previously reported [17]. Concomitant pathologies were observed in 2 patients (patients 3 and 19) in the form of argyrophilic grain pathology or as primary age-related tauopathy with mild or without β-amyloid deposits.…”
Section: Resultsmentioning
confidence: 99%
“…A family history of ALS or FTD was not always seen in those with a causative mutation. A recent exome-wide sequencing study on patients with MND-FTD reported similar rates of mutation and revealed a highly heterogeneous mutation landscape in MND-FTD patients [17]. Cumulative evidence indicates a high genetic background underlying the co-occurrence of MND and FTD, and suggests that testing ALS- and FTD-associated genetic loci should be considered with those patients, regardless of any family history of the disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…ALS is a complex multisystem neurodegenerative disease seen in comorbidity with a wide range of cognitive and behavioral abnormalities, ranging 15 to 50% of cases (Montuschi et al, 2015;Cui et al, 2015), and particularly overlapping with frontotemporal dementia (FTD) (Lillo and Hodges, 2010). Possible pathogenic mutations in ERBB4 gene has been also recently described in concomitant ALS and FTD (Dols-Icardo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%